The Resource Curse and Rentier States in the Caspian Region: A Need for Context Analysis - Hannes Meissner (German Institute of Global and Area Studies (GIGA), 2010)
Although much attention is paid to the Caspian region with regard to energy issues, the domestic consequences of the region's resource production have so far constituted a neglected field of research. A systematic survey of the latest research trends in the economic and political causalities of the resource curse and of rentier states reveals that there is a need for context analysis. In reference to this, the paper traces any shortcomings and promising approaches in the existent body of literature on the Caspian region. Following on from this, the paper then proposes a new approach; specifically, one in which any differences and similarities in the context conditions are captured. This enables a more precise exploration of the exact ways in which they form contemporary post-Soviet Caspian rentier states. – – Obwohl der Region am Kaspischen Meer im Zuge von Energiediskursen große Aufmerksamkeit zuteil wird, stellen die innerstaatlichen Folgen der Ressourcenproduktion in der Region ein bislang vernachlässigtes Forschungsfeld dar. Ein systematischer Überblick über die jüngsten Forschungstrends zu wirtschaftlichen und politischen Kausalzusammenhängen des Ressourcenfluchs und zu Rentierstaaten offenbart die Notwendigkeit von Kontextanalysen. Hierauf Bezug nehmend, analysiert der Aufsatz sowohl die Mängel als auch viel versprechende Ansätze in der betreffenden Literatur zur Region am Kaspischen Meer. Der Aufsatz stellt letztendlich einen neuen Ansatz vor, der Unterschiede und Gemeinsamkeiten in den Kontextbedingungen erfasst, um zu erforschen, wie diese die gegenwärtigen post-sowjetischen Rentierstaaten in der Region am Kaspischen Meer tatsächlich prägen.
Keywords: 300; resource curse; rentier state; Caspian Sea; natural resources; post-Soviet states; democracy; socioeconomic development; institutions; Rohstoffressourcen; Rent Seeking; Public Choice; Kaspisches Meer; Zentralasien